Markers of Focal and Diffuse Nonischemic Myocardial Fibrosis Are Associated With Adverse Cardiac Remodeling and Prognosis in Patients With Hypertension: The REMODEL Study. Issue 8 (23rd May 2022) - Iyer, Nithin R.; Le, Thu-Thao; Kui, Michelle S.L.; Tang, Hak-Chiaw; Chin, Chee-Tang; Phua, Soon-Kieng; Bryant, Jennifer A.; Pua, Chee-Jian; Ang, Briana; Toh, Desiree-Faye; Aw, Tar-Choon; Lee, Chi-Hang; et al.
Abstract : Background: The prognostic significance of focal and diffuse myocardial fibrosis in patients with cardiovascular risk factors is unclear. Methods: REMODEL (Response of the Myocardium to Hypertrophic Conditions in the Adult Population) is an observational cohort of asymptomatic patients with essential hypertension. All participants underwent cardiovascular magnetic resonance to assess for myocardial fibrosis: nonischemic late gadolinium enhancement (LGE), native myocardial T1, postcontrast myocardial T1, extracellular volume fraction including/excluding LGE regions, interstitial volume (extracellular volume×myocardial volume), and interstitial/myocyte ratio. Primary outcome was a composite of first occurrence acute coronary syndrome, heart failure hospitalization, strokes, and cardiovascular mortality. Patients were recruited from February 2016 and followed until June 2021. Results: Of the 786 patients with hypertension (58±11 years; 39% women; systolic blood pressure, 130±14 mm Hg), 145 (18%) had nonischemic LGE. Patients with nonischemic LGE were more likely to be men, have diabetes, be current smokers, and have higher blood pressure ( P <0.05 for all). Compared with those without LGE, patients with nonischemic LGE had greater left ventricular mass (66±22 versus 49±9 g/m 2 ; P <0.001), worse multidirectional strain ( P <0.001 for all measures), and elevated circulating markers of myocardial wall stress and myocardial injury, adjusted for potential confounders. Twenty-four patients had primary outcome over 39 (30–50) months of follow-up. Of all the cardiovascular magnetic resonance markers of myocardial fibrosis assessed, only nonischemic LGE (hazard ratio, 6.69 [95% CI, 2.54–17.60]; P <0.001) and indexed interstitial volume (hazard ratio, 1.11 [95% CI, 1.04–1.19]; P =0.002) demonstrated independent association with primary outcome. Conclusions: In patients with hypertension, myocardial fibrosis on cardiovascular magnetic resonance is associated with adverse cardiac remodeling and outcomes.